Plasma First Resuscitation Reduces Lactate Acidosis, Enhances Redox Homeostasis, Amino Acid and Purine Catabolism in a Rat Model of Profound Hemorrhagic Shock. Issue 2 (August 2016) - D'Alessandro, Angelo; Moore, Hunter B.; Moore, Ernest E.; Wither, Matthew J.; Nemkov, Travis; Morton, Alexander P.; Gonzalez, Eduardo; Chapman, Michael P.; Fragoso, Miguel; Slaughter, Anne; Sauaia, Angela; Silliman, Christopher C.; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : ABSTRACT: The use of aggressive crystalloid resuscitation to treat hypoxemia, hypovolemia, and nutrient deprivation promoted by massive blood loss may lead to the development of the blood vicious cycle of acidosis, hypothermia, and coagulopathy and, utterly, death. Metabolic acidosis is one of the many metabolic derangements triggered by severe trauma/hemorrhagic shock, also including enhanced proteolysis, lipid mobilization, as well as traumatic diabetes. Appreciation of the metabolic benefit of plasma first resuscitation is an important concept. Plasma resuscitation has been shown to correct hyperfibrinolysis secondary to severe hemorrhage better than normal saline. Here, we hypothesize that plasma first resuscitation corrects metabolic derangements promoted by severe hemorrhage better than resuscitation with normal saline. Ultra-high-performance liquid chromatography-mass spectrometry-based metabolomics analyses were performed to screen plasma metabolic profiles upon shock and resuscitation with either platelet-free plasma or normal saline in a rat model of severe hemorrhage. Of the 251 metabolites that were monitored, 101 were significantly different in plasma versus normal saline resuscitated rats. Plasma resuscitation corrected lactate acidosis by promoting glutamine/amino acid catabolism and purine salvage reactions. Plasma first resuscitation may benefit critically injured trauma patients by relieving the lactate burden and promoting other non-clinically measured metabolic changes. In the light of our results, we propose that plasma resuscitation may promote fueling of mitochondrial metabolism, through the enhancement of glutaminolysis/amino acid catabolism and purine salvage reactions. The treatment of trauma patients in hemorrhagic shock with plasma first resuscitation is likely not only to improve coagulation, but also to promote substrate-specific metabolic corrections.